Treatment of advanced gallbladder cancer: A SEER‐based study. (13th November 2019) - Mao, Weipu; Deng, Fang; Wang, Dongyan; Gao, Li; Shi, Xiuquan
Abstract: Purpose: The treatment of advanced gallbladder cancer (GBC) remains controversial. Therefore, the purpose of this study was to explore treatment choices for advanced GBC. Methods: We identified four different treatments from the surveillance, epidemiology, and end results (SEER) database: surgery, chemotherapy (CT), surgery and chemotherapy (Surgery + CT), and no surgery/no chemotherapy (No surgery/No CT). Kaplan‐Meier method and Cox proportional hazards regression method were used to determine the risk factors for overall survival (OS) and cancer‐specific survival (CSS). In addition, patients in AJCC stages III and IV stage were matched with 1:1 propensity score matching (PSM) for diagnosis age, race, marital status, histological type, tumor grade, and treatment pattern to decrease the possibility of selection bias. Results: A total of 288 AJCC stage III patients and 4239 AJCC stage IV patients with advanced GBC were identified from the SEER database between 2004 and 2015. Treatment pattern was an independent risk factor for patients with advanced GBC. For all patient, AJCC stage III patients and AJCC stage IV patients, "Surgery + CT" treatment minimized the OS and CSS in advanced GBC patients. In addition, after the PSM analysis, the "Surgery + CT" treatment still significantly decreased patient OS and CSS. Conclusions: "Surgery + CT" treatment can provide survival benefits for patients with advanced GBC. In addition, "Surgery + CT" treatment was not fully utilized and may further improve the survival rate of GBC patients. Abstract : Surgery and chemotherapy (Surgery + CT) can provide survival benefits for patients with advanced gallbladder cancer (GBC). The treatment of "Surgery + CT" is not fully utilized, and the combined use of "Surgery + CT" can improve the survival rate of GBC patients.